Barriers to implementation of Tuberculosis infection control amongst South African Health Care Workers - Adeleke, Oluwatoyin (Health Economics Unit, 2014)
HIV co-infection and drug resistance worsen the burden of Tuberculosis in South Africa. Infectious TB cases, often undiagnosed and untreated, are commonly found in health facilities increasing the likelihood of health-care associated TB. Health Care Workers (HCWs; and clients) are particularly at risk of TB infection in health care facilities; such risk characterises TB as a dual public health threat; first as a communicable disease and second as an occupational health hazard. Tuberculosis infection control (TBIC) measures may reduce the risk of TB transmission in health care settings, yet HCWs face challenges implementing TBIC measures. There is a gap in operational research seeking to understand the barriers to TBIC implementation among HCWs. There is, therefore, an urgent need to generate qualitative data, using a behavioural and sociological approach that provides insight to TBIC implementation challenges among HCWs. This case study research explored the barriers to TBIC implementation among HCWs in Khayelitsha clinics. Among professional and lay HCWs, data was collected by direct observation, interviews, focus group discussions and review of previous TBIC clinic assessment reports. The data was analysed using thematic analysis and interpretive analysis. This minor dissertation is in four parts. The protocol (Part A) presents the concept note of the study and its methodology. A structured literature review (Part B) provides a background and broadly reviews previous research and findings on Tuberculosis infection control. The journal ready article (Part C) presents the study findings, while Part D presents the study tools and related resources (appendices). Although most HCWs recognise the importance of TBIC in preventing health-care associated TB, they commonly believed that the TB transmission risk is only significant in clinic areas where known TB patients are found, and as such emphasise TBIC measures in those areas. Measures such as use of respirators and masks are mostly prioritized by HCWs ahead of administrative and environmental measures that are potentially more effective in reducing TB infection. Barriers to TBIC implementation identified include: inadequate HCW training on TBIC, a non-responsive compensation policy and the perception that a busy clinic schedule leaves no time for TBIC implementation. Resource availability, adequate human resources and leadership were further identified as enablers for TBIC implementation.